Factors effecting the outcomes of artificial urinary sphincter placement: a single-center study - Aydos, Mustafa Murat; Çaglayan, Volkan (The European Research Journal, 2020)
Objectives: To evaluate the patients who underwent artificial urinary sphincter (AUS) placement and report outcomes of the procedure. Methods: From March 2008 to February 2017, the data of patients who have undergone AUS placement were evaluated retrospectively. Age, body-mass index (BMI), comorbidities, education level, previous radiotherapy (RT) history of the patients were recorded. Cognitive status was examined using the Mini Mental Status Examination test (MMSE). International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF) was completed pre- and post-operatively. Quality of life and satisfaction of patients were evaluated using Patient Global Impression of Improvement (PGI-I) scale. To analyze factors effecting success and revision rates, patients were grouped according to age, BMI, comorbidities, smoking habbit, previous RT history and etiology of incontinence. Treatment success was defined as requirement of ≤ 1/day. Results: A total of 61 patients were included in the study and each were cognitive intact (MMSE > 25). ICIQ-SF significantly improved in postoperative period (p < 0.001). PGI-I median score was 1 (1-4) in postoperative period. Success rate was 96.7% (n = 59) and 47 (77%) patients were complete dry. Revision requirement occured in 10 (16.4%) patients. When patient groups were compared according to the success and revision rates; presence of BMI > 25 kg/m2 was the only significant factor associated with revision requirement and there was no significant factor associated with success status. Conclusion: AUS placement is a safe and effective method in the treatment of post-prostatectomy incontinence (PPI). Success and revision rates are similar regardless the etiology of PPI. Cognitive functions of patients may be crucial in the postoperative satisfaction status.